Planet Hunters TESS III: two transiting planets around the bright G dwarf HD 152843. Issue 2 (12th May 2021) - Eisner, N L; Nicholson, B A; Barragán, O; Aigrain, S; Lintott, C; Kaye, L; Klein, B; Miller, G; Taylor, J; Zicher, N; Buchhave, L A; Caldwell, D A; et al.
ABSTRACT: We report on the discovery and validation of a two-planet system around a bright ( V  = 8.85 mag) early G dwarf (1.43  R⊙, 1.15  M⊙, TOI 2319) using data from NASA's Transiting Exoplanet Survey Satellite ( TESS ). Three transit events from two planets were detected by citizen scientists in the month-long TESS light curve (sector 25), as part of the Planet Hunters TESS project. Modelling of the transits yields an orbital period of $11.6264 _{ - 0.0025 } ^ { + 0.0022 }$  d and radius of $3.41 _{ - 0.12 } ^ { + 0.14 }$  R⊕ for the inner planet, and a period in the range 19.26–35 d and a radius of $5.83 _{ - 0.14 } ^ { + 0.14 }$  R⊕ for the outer planet, which was only seen to transit once. Each signal was independently statistically validated, taking into consideration the TESS light curve as well as the ground-based spectroscopic follow-up observations. Radial velocities from HARPS-N and EXPRES yield a tentative detection of planet b, whose mass we estimate to be $11.56 _{ - 6.14 } ^ { + 6.58 }$  M⊕, and allow us to place an upper limit of 27.5 M⊕ (99 per cent confidence) on the mass of planet c. Due to the brightness of the host star and the strong likelihood of an extended H/He atmosphere on both planets, this system offers excellent prospects for atmospheric characterization and comparative planetology.